2003
DOI: 10.1002/dys.238
|View full text |Cite
|
Sign up to set email alerts
|

Findings from the International Adult Literacy Survey on the incidence and correlates of learning disabilities in New Zealand: Is something rotten in the state of New Zealand?

Abstract: New Zealand data from the International Adult Literacy Survey were analysed to examine the incidence and correlates of self-reported specific reading learning disability (SRLD). The results showed that 7.7% of New Zealand adults reported having had a learning disability. The ratio of males to females with SRLD was 3:2. Between 40% and 50% of New Zealand adults performed below the minimum level of proficiency required for meeting the complex demands of everyday life in knowledge-based societies. For adults with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…For example, Chapman et al (2003) analysed data from the first administration of the International Adult Literacy Survey in the mid-1990s (Murray, Kirsch, & Jenkins, 1998) and found that approximately 80% of New Zealand adults (16-65 years) with self-reported learning disabilities (7.7% of the total adult population) were performing below the minimum level of literacy proficiency required for meeting the complex demands of every-day workplace and leisure activities in knowledge-based societies . Further, they reported that the literacy performance of younger adults with learning disabilities was the poorest, most likely because these adults commenced school in the early 1960s, when the literature-based approach to literacy instruction was introduced (Nicholson, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Chapman et al (2003) analysed data from the first administration of the International Adult Literacy Survey in the mid-1990s (Murray, Kirsch, & Jenkins, 1998) and found that approximately 80% of New Zealand adults (16-65 years) with self-reported learning disabilities (7.7% of the total adult population) were performing below the minimum level of literacy proficiency required for meeting the complex demands of every-day workplace and leisure activities in knowledge-based societies . Further, they reported that the literacy performance of younger adults with learning disabilities was the poorest, most likely because these adults commenced school in the early 1960s, when the literature-based approach to literacy instruction was introduced (Nicholson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The results are discussed in terms of the lack of official recognition of dyslexia in New Zealand, the whole language orientation of classroom reading instruction, and the inadequacy of Reading Recovery for minimizing reading problems. (Chapman, 1992;Chapman, Tunmer, & Allen, 2003). An attempt in 1986 by a Member of the New Zealand Parliament to introduce legislation to have LD defined, recognized, and provided for within the state education system was opposed by Department of Education officials for three main reasons: (1) there were no legislated categories of special education in New Zealand; (2) the country was in the process of developing a non-categorical, needs-based system of special education, based on a strong mainstreaming approach (Department of Education, 1987), and; (3) the proposed definition of LD, based on the United States PL 94-142 definition (but without the 'exclusion clause') was seen as problematic within the New Zealand educational context.…”
mentioning
confidence: 99%
“…There are major disagreements about the nature and diagnosis of dyslexia, whether it has single or multiple factors and how educators should respond in assisting learners with dyslexia (Chanock, 2007;Chapman et al, 2003;Riddell & Weedon, 2006). Constructs of what constitutes dyslexia come from neurobiological, phonological, educational and social paradigms and affect approaches to working with learners (Chanock, 2007;Pollack, 2005;Riddick, 2001).…”
Section: Disagreement and Confusionmentioning
confidence: 99%
“…In April 2007 the Ministry of Education formally recognised dyslexia as a ''spectrum of learning disabilities'', with a working definition of dyslexia ''to describe a range of persistent difficulties with aspects of reading, writing and spelling'' (Ministry of Education, 2008, p. 2). Estimates of the number of Aotearoa/New Zealanders affected by 'specific learning disability' or 'selfdiagnosed reading disability' are placed at about 7% (Chapman, Tunmer, & Allen, 2003;Ministry of Education, 2006). There are no figures on how many students with dyslexia are now in the Aotearoa/New Zealand education system or how successful they are at obtaining national qualifications.…”
Section: Introductionmentioning
confidence: 99%
“…The IALS methodology is unique in the approach it adopts, measuring comprehension in three different forms, using a weighted probability sampling method which tests over 3000 adults in each of 22 countries, with 3811 in Britain (see for example Chapman, Tunmer, & Allen, 2002 for further details on the methodology). The IALS texts measure comprehension, based on the use of printed and written information to function in society, to achieve goals, and to develop personal skills.…”
Section: Methodsologymentioning
confidence: 99%